Reflect Method Action to develop capacities in business and tax management - Collantes Palomino, Hugo Yvan (2018)
The present research has as general objective to determine to what extent the application of the Reflect ActionMethod achieves the development of capacities in business and tributary management of the farmers ofMonsefú, Reque and Eten; And as specific objectives: perform the validity and reliability test of the datacollection instruments, apply the pretest and post test to evaluate the capacities in Business and taxmanagement, apply the Reflect action. This research is important because the literacy method and itsapproach, influences the significant learning of business and tax management among illiterate people. In thisperspective, a pre - research was developed, the data collection was carried out by applying a pre - test and apost to the sample, the research development was approached from an educational perspective, observing thecurrent situation of the peasants, with Regarding the development of capacities of the business and taxmanagement. Key words: Reflect method action, capacities in business management, capacities in tax management.